The landscape of energy initiatives in sub-Saharan Africa: Going for systemic change or reinforcing the status quo? - Baptista, I; Plananska, J (Elsevier, 2017)
This article examines recent interventions by major players in sub-Saharan Africa’s energy sector and asks whether they acknowledge or seek to address energy as a complex problem and energy systems as socio-technical systems. Several scholars have begun advocating the socio-technical approach to energy by noting that the mainstream conceptualization of energy challenges in strictly technological or economic terms does not capture the complexity and inertia inherent to energy systems. Moreover, the article also seeks to examine how well have recent interventions integrated pro-poor and low-carbon concerns, two of the major tenets of UN’s Sustainable Development Goal 7. Findings suggest that initiatives studied take only partial consideration of key aspects of a socio-technical approach to the energy problem. Nonetheless, the initiatives have taken on board pro-poor and low-carbon concerns to a certain extent. Two main policy implications are drawn from this study: a continued focus on status quo approaches has the potential to generate investment inefficiencies; and an effective low-carbon transition will require a broader discussions about the types of lifestyles people in sub-Saharan Africa aspire to.